The Influence of Glycerol on Mechanical, Thermal and Morphological Properties of Thermoplastic Tapioca Starch Film - Ajiya, Dahiru Adamu; Jikan, Suzi Salwah; Haji A. Talip, Balkis Haji; Badarulzaman, Nur Azam; H. M, Matias-Peralta; Derawi, Darfizzi; Yahaya, Shehu (Journal of Science and Technology, 2017)
Thermoplastic tapioca starch (TPTS) film was made by tape casting. The viscoelastic behaviour, thermal degradation and surface morphology were investigated using Dynamic mechanical analysis (DMA), Thermogravimetric analysis (TGA) and Scanning electron microscope (SEM) respectively. The DMA result shows that the storage modulus as well as loss modulus of the TPTS films with 0, 5, 10, 15 and 20% glycerol appears to reduce with increase in glycerol content due to phase relaxation as a result of molecular interaction of the starch molecules with glycerol molecules. Whereas, tan Î´ shows the effect of temperature is higher on the TPTS film with low glycerol content. The thermal degradation of the TPTS is more susceptible to heat as shown by curve 2(e) for film sample with 20% glycerol, showing that higher glycerol content reduces thermal stability of the film. Even though, lowering of glass transition temperature of the TPTS films took effect with the higher concentration of glycerol which proves ease of processibility and workability of the film. The SEM micrographs of fracture surfaces indicate intermolecular miscibility and surface adhesion increases with higher fraction of glycerol content.